Endophytic fungi: expanding the arsenal of industrial enzyme producers. (1st October 2014) - Corrêa, Rúbia Carvalho Gomes; Rhoden, Sandro Augusto; Mota, Thatiane Rodrigues; Azevedo, João Lúcio; Pamphile, João Alencar; de Souza, Cristina Giatti Marques; Polizeli, Maria de Lourdes Teixeira de Moraes; Bracht, Adelar; Peralta, Rosane Marina
Abstract: Endophytic fungi, mostly belonging to the Ascomycota, are found in the intercellular spaces of the aerial plant parts, particularly in leaf sheaths, sometimes even within the bark and root system without inducing any visual symptoms of their presence. These fungi appear to have a capacity to produce a wide range of enzymes and secondary metabolites exhibiting a variety of biological activities. However, they have been only barely exploited as sources of enzymes of industrial interest. This review emphasizes the suitability and possible advantages of including the endophytic fungi in the screening of new enzyme producing organisms as well as in studies aiming to optimize the production of enzymes through well-known culture processes. Apparently endophytic fungi possess the two types of extracellular enzymatic systems necessary to degrade the vegetal biomass: (1) the hydrolytic system responsible for polysaccharide degradation consisting mainly in xylanases and cellulases; and (2) the unique oxidative ligninolytic system, which degrades lignin and opens phenyl rings, comprises mainly laccases, ligninases and peroxidases. The obvious ability of endophytic fungi to degrade the complex structure of lignocellulose makes them useful in the exploration of the lignocellulosic biomass for the production of fuel ethanol and other value-added commodity chemicals. In addition to this, endophytic fungi may become new sources of industrially useful enzymes such as lipases, amylases and proteases.